Scientific Approach toward Hadith: A Study of Zaglul al-Najjar’s Work - Sri H. Lestari; Atropal Asparina (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
This paper discusses the concept of science in hadith. In appropriation with the spirit of integration-interconnection, although it is not a very new issue appearing nowadays, the encounters between sciences and scriptural texts always invite such curiousity in hadith studies. One of the popular works dealing with sciences in hadith is “al-I`jāz al-‘Ilmī fī al-Sunnah al-Nabawiyyah,” written by an Egyptian geologist, Zaghlūl al-Najjār. This paper examines the topic using analytical-descriptive to the data gathered. This article focuses on answering the question on who, what, and how sciences dialogues with hadith in this book which must be influenced by his social and intellectual background. It also pervades scientific concepts and natural phenomena which is recorded in hadith. Therefore, this mini-research is written to perceive how the author explains Sunnah which presents along with his knowledge of natural sciences. Besides, this study also deals to uncover the implications of the author’s scientific approach to the status and validity of the hadith used in his work. This study shows that al-Najjār explains a hadith using the thematic method and directly includes the hadith text that is to be explained. He also supported his explanation with the Qur’anic verses. He explains the hadīth using various forms of scientific data using research reference sources from East and West.